An Illustrative Case of Bilateral Internal Carotid Artery Occlusion Concomitant with Aneurysm of the Obstructed ICA Reconstituted via Collaterals: Emphasizing the Role of Rescue Collaterals in Decision-Making - Malikov, Azad; Sayin, Bige; Akmangit, Ilkay; Senol, Yigit Can; Daglioglu, Ergun; Belen, Ahmet Deniz (Asian Journal of Neurosurgery, 2023)
In patients with bilateral internal carotid artery (ICA) obstruction, the basilar and ophthalmic arteries become the most critical arteries for brain perfusion, and the location of aneurysm formation may be associated with increased wall shear stress induced by compromised carotid circulation. Consideration of collateral routes may have an impact on therapeutic decisions for patients undergoing extracranial to intracranial (EC-IC) bypass and aneurysm surgery. We report a rare case of a young woman with bilateral ICA occlusion simultaneous with dissecting aneurysm of the obstructed ICA reconstituted via collaterals, emphasizing the functional value of collaterals and therapeutic strategy. We present a young woman with angiographic evidence of cerebrovascular early atherosclerotic disease. A young patient was found to have bilateral ICA occlusion and dissecting aneurysm of the obstructed ICA. A large fusiform aneurysm was clipped. Then, an anastomosis was performed from the left superficial temporal to the M3 segment of the middle cerebral artery. The patient's postoperative course was uneventful, and she was discharged to rehabilitation with no residual sequelae. This case illustrates a rare case of bilateral ICA occlusions, presented with robust collaterals, and dissecting aneurysm of the obstructed ICA reconstituted via collaterals. We also demonstrate excellent surgical clipping of a challenging ICA aneurysm and cerebral bypass surgery.
Keywords: internal carotid artery occlusion; multiple aneurysms; collaterals; ICA bifurcation aneurysm; STA-MCA bypass